Right atrial thrombus formation in a dog after successful electrical cardioversion for atrial fibrillation - Marta Karn; Brianna M. Potter; Brian A. Scansen; June A. Boon; Viktor Szatmári (Journal of Veterinary Internal Medicine, 2023)
Abstract Right atrial masses in dogs are commonly diagnosed as malignant tumors. This report describes a dog with a right atrial mass that appeared after successful electrical cardioversion of atrial fibrillation and resolved with antithrombotic treatment. A 9‐year‐old mastiff was presented for acute vomiting, and occasional cough of several weeks' duration. Ultrasonographic and radiographic examinations of the abdomen and chest identified mechanical ileus, as well as pleural effusion and pulmonary edema, respectively. Echocardiography indicated a dilated cardiomyopathy phenotype. During anesthetic induction for laparotomy, atrial fibrillation developed. Electrical cardioversion successfully restored sinus rhythm. An echocardiogram performed 2 weeks later disclosed a right atrial mass, which had not been apparent before cardioversion. Repeat echocardiography after 2 months of clopidogrel and enoxaparin treatment failed to detect the mass. Intra‐atrial thrombus formation is possible after successful cardioversion of atrial fibrillation and should be considered as a differential diagnosis for echocardiographically detected atrial masses.